2009
DOI: 10.1519/jsc.0b013e3181a4e88e
|View full text |Cite
|
Sign up to set email alerts
|

Functional Performance, Maximal Strength, and Power Characteristics in Isometric and Dynamic Actions of Lower Extremities in Soccer Players

Abstract: The purposes of the present study were to determine muscle strength and power output characteristics in a group of professional soccer players and to identify their relationships with 2 functional performance tests (vertical jumping height and 15-m sprint time). Maximal strength and power indices attained against different loads in barbell back squat exercise, isometric maximal force of the knee extensor and plantar flexor muscles, isokinetic peak torque of the knee extensors muscles, vertical jumping height i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
110
5
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 28 publications
9
110
5
4
Order By: Relevance
“…10 Early research by Wilson et al 11 found no relationship (r = −0.46 to 0.17; p > 0.05) between single joint isometric strength and 30 m sprint performance. In agreement with these findings, Requena et al 12 observed no relationship (r = −0.35; p > 0.05) between isometric strength with subjects sat in a custommade dynamometric chair, and 15 m sprint performance. However, West et al 13 found significant correlations between isometric mid-thigh pull (IMTP) RFD, absolute and relative PF at 100 ms, and 10 m sprint performance (r = 0.66, 0.54, and 0.68, respectively).…”
Section: Introductionmentioning
confidence: 61%
“…10 Early research by Wilson et al 11 found no relationship (r = −0.46 to 0.17; p > 0.05) between single joint isometric strength and 30 m sprint performance. In agreement with these findings, Requena et al 12 observed no relationship (r = −0.35; p > 0.05) between isometric strength with subjects sat in a custommade dynamometric chair, and 15 m sprint performance. However, West et al 13 found significant correlations between isometric mid-thigh pull (IMTP) RFD, absolute and relative PF at 100 ms, and 10 m sprint performance (r = 0.66, 0.54, and 0.68, respectively).…”
Section: Introductionmentioning
confidence: 61%
“…These kinds of measurements provide more information concerning body composition and muscle strength, however it makes it difficult to make direct comparisons to other studies as different physiological off-ice tests have been used and correlations between jump tests and isokinetic muscle strength have been reported to be moderate to low (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although we believed this was an important first step, we readily acknowledge that a static contraction is not adequately reflective of the complex interaction of neural activation strategies (both planned and unplanned) and intrinsic muscle properties (eg, musculotendinous stiffness, electromechanical delay) inherent in dynamic tasks when injuries actually occur. Although MVIC strength might shed some light on dynamic movement, only low to moderate correlations have been reported between MVICs of the quadriceps and squat jump 32,42 and countermovement jump in trained male athletes 32,42 and between greater MVIC thigh strength and greater muscular energy absorption during a drop-jump landing in women. 10 Hence, although our findings revealed no acute changes in isometric torque production across the cycle, we cannot rule out possible hormone effects on other aspects of neuromuscular control that contribute to dynamic movement.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature in which researchers generally observed greater strength in postovulatory than in preovulatory phases of the cycle, we expected to observe increases in MVIC torques from the early follicular to the EL and ML phases of the menstrual cycle and to observe the greatest increase with testing in the EL phase shortly after the estradiol peak at ovulation. Although research is conflicting on the relationship between MVIC strength and functional performance 32 and although MVIC strength has not been linked specifically to ACL injury risk, we believed it was important to first assess isometric contractions as a measure of muscle strength so that we could best isolate the basic force-producing capability of each muscle group while minimizing the potentially confounding effects of larger amounts of antagonist activity 33 often observed with higher-speed isokinetic contractions. 34 …”
Section: Journal Of Athletic Trainingmentioning
confidence: 99%